Mechanical system of IoT-based automatic aquarium - Muhammad Nasri, Ahmad Nazuki@Marzuki (2021)
Nowadays fish-keeping is become trending. People from all ages like to keep fish for entertainment purposes, decorative or as a hobby in their homes, workplaces, mall, and hotels. There are many types of fish used for fish keeping such as marine, fresh water tropical, cold water and brackis. Depends with what kind of fish to decide with type of water need to use. But fish keeping need to take it serious action to maintained the water level, water needs to be changed, the fish needs to be fed, the temperature must be in optimum condition and water level of the aquarium should always be enough. In this project, smart aquarium with internet of things (IOT)application has been design to make life easier and fancier to monitor the aquarium. This aquarium consist the automatic water pump that already combined with filter to reduce and turbidity in the water. To control turbidity, water power of hydrogen level sensor is applied to this project. When water level sense less or more than 7 will notify user in from an applications. In addition, this project also has been designed feeder tank with indicator that notify user when the tank is empty. Next, automatic lamp and temperature sensor is added to this project to support fish growth and fish behavior. All of this features will control by application through a cell phone.